Aliaksei Kazharski: Central Europe Thirty Years after the Fall of Communism. A Return to the Margin? (Czech Journal of International Relations, 2024)
Ondřej Slačálek reviews Aliaksei Kazharski´s new book. According to Slačálek, the book has many promising points of entry for understanding the (re)construction of “Central Europe” as a region, and understanding it from the East rather than (yet again) from the West. However, this potential is realized only partially. As the book does not take the region´s real historical marginality seriously, in it, Central Europe does not become marginal until it deviates from its alleged transition to or place in the supposed Western European mainstream. Slačálek sums up that the book can be read not only as a valuable scholarly contribution to the debate, but also as a document of its time: a time when (at least for many influential analysts) conservative nationalism could look like something  that may be localized on the European “margins” and considered a re-creation of regionalized pathologies of Central Europe, while the western part may be characterized by a “universalist”, “liberal” and “humanitarian” stance. He concludes that this kind of analysis is also a biased construction that might belie the much more complex and richer reality.Central Europe Thirty Years after the Fall of Communism. A Return to the Margin? Lanham: Lexington Books, 2022, 226 pages, ISBN: 978-1-4985-9961-0